The Use of Analgesic and Other Pain‐Relief Drugs to Manage Chronic Low Back Pain: Results from a National Survey. Issue 3 (21st May 2016) - Gouveia, Nélia; Rodrigues, Ana; Ramiro, Sofia; Eusébio, Mónica; Machado, Pedro M.; Canhão, Helena; Branco, Jaime C.
Abstract: Objectives: To analyze and characterize the intake profile of pain‐relief drugs in a population‐based study of adults with chronic low back pain (CLBP). Methods: EpiReumaPt was a cross‐sectional Portuguese population‐based study (10, 661 subjects). Self‐reported active CLBP was considered to be low back pain on the day of enrollment and for ≥ 90 days. Prevalence and profile of analgesic intake was characterized among those self‐reporting active CLBP, taking into account the intensity of pain and the World Health Organization (WHO) analgesic ladder. We further investigated whether the presence of active CLBP was a factor independently associated with the intake of analgesics (adjusted for potential confounders). Results: Among 1, 487 subjects with active CLBP, only 18.7% were using analgesic/pain‐relief drugs. Estimated prevalence was anxiolytics, 14.1%; nonsteroidal anti‐inflammatory drugs (NSAIDs), 12.3%; antidepressants, 10.1%; analgesic, antipyretics, 6.6%; anticonvulsants, 3.4%; central muscle relaxants, 2.6%; and analgesic opioids, 1.6%. Most subjects with severe pain were in the first step of the WHO analgesic ladder: NSAIDs plus anxiolytics (4.6%), NSAIDs plus antidepressants (3.2%), or NSAIDs plus muscle relaxants (2.5%). The presence of active CLBP was significantly associated with the intake of all therapeutic groups: antidepressants (odds ratio [OR] = 12.56; P < 0.001); centrally acting muscle relaxants (OR = 12.01; P < 0.001); anticonvulsants (OR = 9.27; P < 0.001); anxiolytics, sedatives, and hypnotics (OR = 8.86; P < 0.001); NSAIDs (OR = 8.56; P < 0.001); and analgesic opioids (OR = 8.13; P < 0.001). Conclusion: Analgesic/pain‐relief drug intake in patients with active CLBP was very low, even for those with severe pain. The WHO analgesic ladder was carefully followed, with an extremely conservative use of analgesic opioids even for those with severe pain.